2019
DOI: 10.29252/rap.10.24.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamins C and E on Some Sperm Characteristics in Varamini Rooster in Cold Conditon

Abstract: A total of 36 breeder roosters were divided to 4 dietary treatments which were consisting of 3 pens with 3 birds per pen. Treatments were as follow: 1) Control diet without vitamins C and vitamin E, 2) Cdiet containing 1000 mg/kg vitamin C, 3) E-diet containing 1000 mg/kg vitamin E and 4) E+C diet containing vitamins C and E (1000mg/kg of each vitamin). Diets were fed to the roosters for a 28 d experimental period. Sperm collection was done by rubbing the belly method, and semen was diluted by of solution tris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“… Cerolini et al (2006) reported that the addition of 300 mg of vitamin E to the diet of Cobb broiler breeder roosters significantly increased sperm volume and concentration. Similar findings were reported by Darestani et al (2019) who added 1,000 mg of vitamin E to the Varamini roosters' diet. Our findings in this part of study agree with Attia and Kamel (2012) who investigated the impact of soybean lecithin on rabbit sperm quality, and they found higher semen volume and sperm concentration in the diet supplemented with 1 and 1.5% soybean lecithin.…”
Section: Resultssupporting
confidence: 86%
“… Cerolini et al (2006) reported that the addition of 300 mg of vitamin E to the diet of Cobb broiler breeder roosters significantly increased sperm volume and concentration. Similar findings were reported by Darestani et al (2019) who added 1,000 mg of vitamin E to the Varamini roosters' diet. Our findings in this part of study agree with Attia and Kamel (2012) who investigated the impact of soybean lecithin on rabbit sperm quality, and they found higher semen volume and sperm concentration in the diet supplemented with 1 and 1.5% soybean lecithin.…”
Section: Resultssupporting
confidence: 86%